Fast analysis of 19 anabolic steroids in bovine tissues by high performance liquid chromatography with tandem mass spectrometry. Issue 21 (18th September 2019) - Wozniak, Barbara; Matraszek–Zuchowska, Iwona; Klopot, Alicja; Posyniak, Andrzej
Abstract: For the detection of 19 steroid hormones in bovine muscle, a fast and sensitive liquid chromatography with electrospray ionization tandem mass spectrometry method was developed using both positive and negative ionization mode. Chromatographic separation on Poroshell 120‐EC C18 column was achieved in less than 10 min using isocratic elution of mobile phase of acetonitrile/methanol/water. The compounds were extracted from muscle tissue using ethyl acetate and quick, easy, cheap, effective, rugged, and safe technique. The purification of the obtained extract was performed by dispersive solid‐phase extraction with sorbents C18, primary secondary amine and magnesium sulphate. The method was validated in accordance with the Commission Decision 2002/657/EC. For all steroids tested good recoveries were obtained (from 51.2 to 121.4%) in the concentration range from decision limits until 5 µg/kg. The values of decision limits and the detection capabilities for individual compounds were in the range 0.10–0.48 and 0.17–0.95 µg/kg, respectively. The method was characterized by satisfactory linearity for most compounds (correlation coefficients   > 0.99) and the reproducibility was lower than 35%. The elaborated procedure has met the criteria for confirmatory methods and is currently used in the official control of hormones.